Immunogenicity testing of HIV-1 envelope glycoprotein complexes (Env-2dCD4S60C) in Chinese-origin rhesus macaques - Pereira, Roberto Carlos Rebelo (My University, 2021)
A key goal in development of preventative HIV-1 vaccines is the ability to elicit broadly neutralizing antibodies (bNAbs) following vaccination. The target of these bNAbs is the only exposed protein on the surface of the HIV-1 virion, the trimeric HIV-1 envelope glycoprotein (Env). Our research group previously developed a modified two-domain CD4 molecule (2dCD4S60C) that binds with greater affinity to HIV-1 Env glycoproteins through the formation of a stabilizing disulphide bridge. This allowed us to generate stable immunogen complexes suitable for immunizations in animal models. We previously showed that rabbits immunized with Env2dCD4S60C complexes elicit potent bNAbs targeting clinically relevant tier-2 HIV-1 pseudoviruses in vitro. These neutralizing responses were generated regardless of the form (monomeric and trimeric Env) or viral subtype (subtype B and C) of the Env glycoprotein in complex with 2dCD4S60C and were noted to be anti-CD4 in nature. This study describes immunogenicity testing of the Env-2dCD4S60C complex in a non-human primate model (NHP), the Chinese-origin rhesus macaque. Trimeric HIV-1 Env glycoproteins based on a consensus sequence of subtype C founder viruses (gp140FVCGCN4t(+)) and 2dCD4S60C were expressed using mammalian and bacterial cell expression systems. The gp140FVCGCN4t(+) and 2dCD4S60C proteins were purified using lectinaffinity, nickel-affinity and size-exclusion chromatography. Immunogen complexes were then generated under reducing conditions. Immunogenicity of gp140FVCGCN4t(+), gp140FVCGCN4t(+)- 2dCD4S60C (Env-2dCD4 S60C) and 2dCD4 S60C was evaluated in genetically characterized Chineseorigin rhesus macaques (n=7) following a six-dose, four-month vaccination regimen. Breadth and potency of vaccinated macaque sera was evaluated in a TZM-bl pseudovirion neutralization antibody assay. Fourteen pseudoviruses, including the twelve tier-2 HIV-1 Env Global Panel viruses, and an infectious tier-2 SIV/HIV-1 chimeric virus (SHIV-1157ipd3N4), were tested against. Basic mapping of the target of the neutralizing responses generated in NHPs was done using various recombinant CD4 molecules to deplete sera of anti-CD4 antibody responses, and then tested in the TZM-bl pseudovirion neutralization antibody assay. Two years following the vaccination regimen, the NHPs were vaccinated with a booster immunization and subsequently challenged using a low-dose intra-rectal SHIV challenge using SHIV-1157ipd3N4. Env-2dCD4S60C complex immunized NHPs (n=4) developed bNAb responses by day 74 of the vaccination regimen following four immunizations, neutralizing 11/12 of the HIV-1 Env Global Panel of pseudoviruses with titres above 1:100, with a geometric mean titre of 1:356 for the entire group against the panel. In contrast, a single macaque that received gp140FVCGCN4t(+)-only, developed no neutralizing titres against the HIV-1 Env Global Panel, while the 2dCD4S60C-only immunized macaques (n=2) displayed similar breadth to the complex group but with lower potency (1:60). Mapping of the target of the responses of the sera using recombinant CD4 proteins to deplete sera of anti-CD4 antibodies resulted in a reduction in neutralizing potency of sera from Env-2dCDS60C immunized NHPs, with a complete loss of neutralizing potency in one of the sera tested. Two years later, neutralizing titres were no longer detectable in the NHPs, but a booster immunization returned antibody titres to neutralizing levels after two weeks, to levels previously seen. Following booster immunizations, the NHPs were administered ten low-dose intra-rectal SHIV inocula over a 10-week period. CD4+ T-cell counts were monitored using flow cytometry and SHIV viral RNA loads were monitored using RT-PCR. Infection with, or protection from the SHIV-1157ipd3N4 challenges, remained inconclusive. The unique Env-2dCD4S60C complexes elicit potent and broad neutralizing antibody responses in Chinese-origin rhesus macaques against clinically relevant tier-2 HIV-1 pseudoviruses. These neutralizing antibody responses are primarily anti-CD4 in nature, with the precise mechanism of antibody mediated neutralization requiring further delineation. Future work includes assessing whether these elicited anti-CD4 antibody responses are immunotoxic in the vaccinated subject, as well as further proof of concept SHIV-challenge studies (using vaccinated NHPs), to support the advancement of these Env-2dCD4 S60C immunogens into human clinical testing.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa, 2021